Upaya Meningkatkan Hasil Belajar Fiqih Melalui Metode Demonstrasi Pada Siswa Kelas VII B Madrasah Tsanawiyah Hidayatul Mubtadiin Jati Agung Lampung Selatan - Dwi Febriani; Tamyis Tamyis; Anita Anita (Journal on Education, 2024)
The educational process uses methods according to the material, methods are tools or techniques that are often used by a teacher in delivering a lesson. With the method, educators will be more creative and in presenting a lesson material, students' interest in learning will be greater by choosing the right learning method, one of which is by implementing this demonstration method and greatly supports teaching and learning activities in increasing students' interest in learning. Regarding the above, the focus of the research and the purpose of this study is to describe the application of the demonstration method in increasing students' interest in learning in the subject of fiqh. This research was conducted at MTs Hidayatul Mubtadiin Jati Agung Lampung Selatan in the 2023/2024 Academic Year. This type of research is field research with a qualitative research model. The demonstration method is very appropriate and very effective for learning activities. Based on the results of the research that has been carried out, it can be concluded that from the results of the application of the Demonstration method that has been implemented and practiced and has been running well, both from the activities of students, teachers and from the learning outcomes obtained by students have increased. Learning with the application of the Demonstration Method can be used as a solution to overcome student difficulties. The involvement of students in learning activities shows that the level of student participation in learning is very good. This shows that teachers are able to arouse activeness in the student learning process in the subject of fiqh. Factors that influence efforts to improve fiqh learning outcomes through demonstration methods are influenced by two factors, namely, supporting and inhibiting factors. Supporting factors in students' religious behavior, namely teachers have an important role in the learning process. A teacher, in addition to implementing school operational standards, is also able to improve the skills of the material that must be taught so that students are able to properly digest the lessons taught, in addition to the existence of professional education personnel, there are also adequate facilities and infrastructure that are relatively supportive in various activities. While the inhibiting factor is that this method is less effective if implemented in one lesson hour, because it takes a lot of time to practice it. And some students are less focused when the learning process takes place, and there are still students who chat with their friends, making the classroom atmosphere not conducive